Continuous Cropped Winter Wheat in Northeast Kansas - Dhuyvetter, Kevin C. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on continuous cropped winter wheat production in northeastern Kansas.
MF572_1995_10
Keywords: MF572; Economics; Crops; MF